Tailored measurement setup for the contactless characterization of MEMS resonators at the wafer level - D. Huber; M. Schneider; P. Fulmek; G. Pfusterschmied; U. Schmid (Journal of Sensors and Sensor Systems)
Statistical analysis of microelectromechanical system (MEMS) resonator devices in an early stage of device fabrication is challenging since actuation and sensing of the frequency-dependent response characteristics are often impossible before electrical connections are established. Photo-thermal actuation and optical readout using laser Doppler vibrometry (LDV) are powerful techniques to overcome this problem, enabling a fast, contactless device characterization and thus generating a high amount of data for statistical analysis. This paper reports on a tailored measurement setup for the contactless characterization of pure, monocrystalline silicon MEMS resonators at the wafer level. The presented system combines a precision stage for the movement in all three dimensions, a lightweight vacuum chamber, a laser diode for actuation, and a laser Doppler vibrometer. Details on the hardware and software solutions are discussed, and the high potential of the described setup is demonstrated by measuring hundreds of devices fabricated on one silicon-on-insulator (SOI) wafer. First tests show that thickness variations in the silicon device layer influence the resonance frequency of devices across the wafer and that different loss mechanisms dominate different out-of-plane modes in plate-shaped MEMS resonators.